Characterization of circular RNAs landscape in multiple system atrophy brain. Issue 3 (5th September 2016) - Chen, Bei Jun; Mills, James D.; Takenaka, Konii; Bliim, Nicola; Halliday, Glenda M.; Janitz, Michael
Abstract: Circular RNAs (circRNAs) have been recently identified as a naturally occurring family of widespread and diverse endogenous non‐coding RNAs that may regulate gene expression in mammals. They are unusually stable RNA molecules with cell type‐ or developmental stage‐specific expression patterns. However, the role of circRNAs in pathology of complex disease is entirely unknown. Here, we report the specific circular transcriptome in the multiple system atrophy (MSA) brain as determined by RNA sequencing. Five circRNAs, namely IQCK, MAP4K3, EFCAB11, DTNA, and MCTP1, were identified and validated as specifically over‐expressed in MSA frontal cortex. The expression levels of linear transcripts were not significantly altered and thus did not follow the pattern of their circular counterparts. Further analysis of expression of five MSA‐specific circRNAs revealed their over‐expression in the white matter of the MSA cortical tissue. Together, this is the first report describing perturbation of circular transcriptome in α‐synucleinopathies. Abstract : Multiple system atrophy (MSA) is a sporadic neurodegenerative disease of unknown etiology. We investigated genome‐wide profile of circular RNAs (circRNAs) in the frontal cortex of the brain affected by MSA pathology. Comparative analysis with healthy cortical tissue revealed over‐expression of five circular RNAs (circRNAs) specifically in MSA brain. Our study reveals another layer of transcriptome perturbation in neurodegeneration and might potentially provide novel biomarkers for MSA.